Dzyudoshılardıń shınıǵıw procesinde innovaciyalıq texnologiyalardı qollanıw - Sultamuratov, Dj. Qádirbaev B. Aytmuratova B (SCIENCE and SOCIETY, 2024)
The article examines the effectiveness of judokas' use of innovative technologies during training. Also, the individual situation of each athlete and issues of improvement of the coach's skills were analyzed. The results of this research can contribute to the theoretical and practical development of judo, and the improvement of athletes' skills.